Nationalism, Saudade, Myth and History in Fernando Pessoa and Luís Seoane - Fernández Martínez, Antía (Madrygal. Revista de Estudios Gallegos, 2017)
The literary works of Fernando Pessoa (Lisbon, 1888-1935) and Luís Seoane (Buenos Aires, 1910 - A Coruña, 1979) are, apparently, very distant from each other. Nevertheless, they do coincide in two key issues among others: the critical vision of the national (Portuguese and Galician) history and the demythologization process of saudade. The main aim of this paper is to analyze how these elements (history, myth, saudade) relate to each other and how do they establish a conversation with their contemporary nationalisms and the history of their countries.
Keywords: Nationalism; Saudade; Myth; History; Saudosism; Piñeirism; Pessoa; Seoane.